Demographic and Socio-economic Determinants of Financial Literacy : A Literature Review - Nursjanti, Farida; Amaliawiati, Lia (Gema Wiralodra, 2024)
Financial literacy is crucial for anyone seeking to enhance their quality of life while avoiding challenges associated with financial resources. It has emerged as a primary priority for numerous countries today, as it correlates directly with a nation's economic progress. Enhancing financial literacy necessitates a comprehensive grasp of the demographic and socio-economic elements that influence it. This study aimed to examine the demographic and socioeconomic aspects influencing financial literacy. A literature review was the method of research employed in this investigation. Information was reported using descriptive analysis in this regard after reviewing the relevant papers. A review synthesis needed to be formed using this approach. Demographic factors influencing financial literacy encompass age, gender, and educational attainment. A review was undertaken to emphasize the disparities in financial literacy levels by gender across diverse research. Socio-economic factors influencing financial literacy encompass income level and occupation. This study also examined the impact of parental income levels on financial literacy levels. The study's results indicated that demographic factors can influence financial literacy. Notably, disparities in financial literacy exist between men and women. Socio-economic issues significantly impact financial literacy. The results of this study can provide guidance for policy modifications, especially for those who have low financial literacy. These improvements must be implemented to enhance efforts in improving financial literacy by focusing more on demographic and socio-economic issues.